Electrochemical device and electronic device

By using active materials composed of Ni-Mn and Co in the positive electrode sheet of the electrochemical device and adding element B coating in the high voltage region, the problems of energy density, cycle life and safety in the prior art are solved. , an electrochemical device with high energy density, excellent cycle and safety performance is achieved.

CN119325651AActive Publication Date: 2025-01-17NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202380039267.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-01-17
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

While increasing the energy density, existing electrochemical devices are difficult to have long cycle life and high safety, especially under high temperature and high voltage conditions, the risk of structural stability and excessive deliquification is high.

Method used

A positive electrode sheet, including a first positive electrode active material composed of Ni and Mn elements and a second positive electrode active material composed of Co elements, is used to form characteristic peaks between 4.1V and 4.3V and 3.6 by regulating its relative content and structural characteristics. V to 4.0V peaks increase energy density and reduce the risk of excessive deliquency, while adding a cladding of B element to the surface of the first positive electrode active material to inhibit oxygen release and neutralize free lithium.

Benefits of technology

It significantly improves the energy density, cycling performance and safety performance of the electrochemical device, ensuring excellent structural stability and cycling performance under high temperature and high voltage conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325651A_ABST
    Figure CN119325651A_ABST
Patent Text Reader

Abstract

An electrochemical device and an electronic device are provided. The electrochemical device comprises a positive pole piece. The positive pole piece comprises a positive active material layer, and the positive active material layer comprises a first positive active material and a second positive active material. The first positive electrode active material contains Ni element and Mn element, and the second positive electrode active material contains Co element. Wherein the relation curve of the differential dQ / dV of the discharge capacity voltage of the electrochemical device and the voltage V comprises a peak a with the peak position of 4.1 V to 4.3 V and a peak b with the peak position of 3.6 V to 4.0 V. While the energy density of the electrochemical device is improved, the electrochemical device has good cycle performance and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage, and in particular to electrochemical devices and electronic devices. Background Art

[0002] With the widespread application of portable electronic devices, power tools, etc., the market has put forward higher and higher requirements on the comprehensive performance of electrochemical devices (e.g., lithium-ion batteries). For example, electrochemical devices are not only required to have higher energy density to meet the requirements of long battery life, but also to have longer cycle life and higher safety. Therefore, there is an urgent need to develop electrochemical devices with better comprehensive performance. Summary of the invention

[0003] In view of this, the present application provides an electrochemical device and an electronic device to improve the energy density of the electrochemical device while ensuring good cycle life and safety.

[0004] In a first aspect of the present application, an electrochemical device is provided, the electrochemical device comprising a positive electrode plate. The positive electrode plate comprises a positive electrode active material layer, the positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material. The first positive electrode active material contains Ni and Mn elements, and the second positive electrode active material contains Co elements. The relationship curve between the capacity voltage differential dQ / dV and the voltage V of the electrochemical device discharge includes a peak a with a peak position between 4.1V and 4.3V and a peak b with a peak position between 3.6V and 4.0V. In the electrochemical device of the present application, peak a mainly depends on the first positive electrode active material, and peak b mainly depends on the second positive electrode active material. The first positive electrode active material has a characteristic peak a relative to the second positive electrode active material in the high voltage region of the electrochemical device discharge, which can enable the electrochemical device to have a higher reversible discharge capacity in the high voltage region, thereby greatly improving the energy density of the electrochemical device; at the same time, since the amount of lithium desorption of the first positive electrode active material in the high voltage region is relatively high, the risk of excessive lithium desorption of the second positive electrode active material in the high voltage region can be reduced, thereby improving the structural stability of the second positive electrode active material at high temperature and high voltage, and due to the presence of oxygen vacancies on the surface of the first positive electrode active material itself, its surface oxygen release can be inhibited, so that it still has a higher structural stability at high temperature and high voltage, thereby enabling the electrochemical device to have both good cycle performance and safety performance.

[0005] In some embodiments, the peak area of ​​peak a is S a , the peak area of ​​peak b is S b , satisfying: 0.4≤S a / S b ≤1. By adjusting the relative content of the first positive electrode active material and the second positive electrode active material, the area ratio of peak a to peak b is S a / Sb Meeting the above range can significantly improve the energy density of the electrochemical device while enabling the electrochemical device to have both excellent cycle performance and safety performance. a / S b ≤0.65.

[0006] In some embodiments, when the electrochemical device is in a fully charged state, the positive electrode plate is characterized by X-ray diffraction, and has two diffraction peaks in the range of 18° to 19.5°, which are diffraction peak A and diffraction peak B from low angle to high angle, and the peak intensity of diffraction peak A is I A , the peak intensity of diffraction peak B is I B , satisfying: 1.2≤I B / I A ≤5. Wherein, the diffraction peak A corresponds to the first positive electrode active material, the diffraction peak B corresponds to the second positive electrode active material, and I B / I A Meeting the above range can significantly improve the energy density of the electrochemical device while enabling the electrochemical device to have both excellent cycle performance and safety performance. B / I A ≤5.

[0007] In some embodiments, the first positive electrode active material includes a lithium nickel manganese composite oxide, and the second positive electrode active material includes a lithium cobalt composite oxide.

[0008] In some embodiments, the first positive electrode active material is a secondary particle aggregated from primary particles.

[0009] In some embodiments, the first positive active material has an average diameter of 6 μm to 14 μm.

[0010] In some embodiments, the second positive active material is a primary particle.

[0011] In some embodiments, the second positive active material has an average diameter of 10 μm to 25 μm.

[0012] In some embodiments, in a cross section in the thickness direction of the positive electrode active material layer, the area of ​​the first positive electrode active material in the region of 127 μm×34 μm is S1, and the area of ​​the second positive electrode active material is S2, satisfying: 1≤S2 / S1≤7. S2 / S1 satisfies the above range, which can greatly improve the energy density of the electrochemical device while making the electrochemical device have excellent cycle performance and safety performance. Further, in some embodiments, 3.4≤S2 / S1≤6.8.

[0013] In some embodiments, the first positive electrode active material further contains an M1 element, M1 includes at least one of Na or K, based on the metal elements other than the Li element and the M1 element in the first positive electrode active material, the molar percentage of the Ni element in the first positive electrode active material is a1, the molar percentage of the Mn element is b1, and the molar percentage of the M1 element is c1, satisfying: 30%≤a1≤70%, 30%≤b1≤70%, 0.1%≤c1≤15%. The doping of the M1 element enables the first positive electrode active material to have good structural stability at high temperature and high voltage, thereby improving the cycle performance and safety performance of the electrochemical device.

[0014] In some embodiments, the first positive electrode active material includes a substrate and a coating layer located on the surface of the substrate, wherein the coating layer contains element B. The coating layer containing the boron compound can neutralize the free lithium on the surface of the substrate on the one hand, and on the other hand, can eliminate HF generated by the decomposition of lithium salts or other side reactions in the electrochemical device, reduce the corrosion of HF on the electrode material and the current collector, and thus improve the cycle performance and high temperature storage performance of the electrochemical device.

[0015] In some embodiments, the coating layer comprises a B-containing oxide.

[0016] In some embodiments, based on the metal elements other than the Li element and the M1 element in the first positive electrode active material, the molar percentage of the B element in the first positive electrode active material is d1, and 0.5%≤d1≤10%.

[0017] In some embodiments, the first cathode active material has a layered crystal structure belonging to the R-3m space group. In some embodiments, the first cathode active material includes Li x1 M1 m Ni y1 Mn z1 B k R1 q1 O 2±n1 T1 n1 , 0.6≤x1≤1.2, 0.001≤m≤0.15, 0.3≤y1≤0.7, 0.3≤z1≤0.7, 0≤k≤0.1, 0≤q1≤0.2, 0≤n1≤0.2, wherein the element M1 includes at least one of Na or K, the element R1 includes at least one of Co, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and the element T1 includes at least one of F, Cl, Br, I or N.

[0018] In some embodiments, based on the metal elements other than Li in the second positive electrode active material, the molar percentage of the Co element in the second positive electrode active material is a2, satisfying: 80%≤a2≤100%.

[0019] In some embodiments, the second positive electrode active material further includes an M2 element, M2 includes at least one of Ni, Mn, Al, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and based on the metal elements other than Li element in the second positive electrode active material, the molar percentage of the M2 element in the second positive electrode active material is b2, satisfying: 0.1%≤b2≤20%.

[0020] In some embodiments, the second cathode active material has a layered crystal structure belonging to the R-3m space group. In some embodiments, the second cathode active material includes Li x2 Co y2 M2 z2 O 2±n2 T2 n2 , 0.6≤x2≤1.2, 0.8≤y2≤1, 0≤z2≤0.2, 0≤n2≤0.2, wherein element M2 includes at least one of Ni, Mn, Al, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and element T2 includes at least one of F, Cl, Br, I or N.

[0021] In a second aspect of the present application, an electronic device is also provided, comprising the above-mentioned electrochemical device. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and a person skilled in the art can also obtain other embodiments based on these drawings.

[0023] Figure 1 is a discharge curve of the electrochemical device of Example 1 of the present application;

[0024] Figure 2 A curve showing the relationship between the capacity-voltage differential dQ / dV and the voltage V of the electrochemical device of Example 1 of the present application during discharge;

[0025] Figure 3This is the X-ray diffraction (XRD) spectrum of the positive electrode sheet of the electrochemical device in Example 1 of the present application when it is fully discharged. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0027] In a first aspect of the present application, an electrochemical device is provided, the electrochemical device comprising a positive electrode plate. The positive electrode plate comprises a positive electrode active material layer. The positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material. The first positive electrode active material comprises Ni and Mn elements, and the second positive electrode active material comprises Co elements. The relationship curve between the capacity-voltage differential dQ / dV and the voltage V of the electrochemical device during discharge comprises a peak a with a peak position between 4.1V and 4.3V and a peak b with a peak position between 3.6V and 4.0V. Among them, peak a mainly depends on the first positive electrode active material, and peak b mainly depends on the second positive electrode active material. The first positive electrode active material has a characteristic peak a in the high voltage region of the electrochemical device discharge relative to the second positive electrode active material, which can make the electrochemical device have a higher reversible discharge capacity in the high voltage region, thereby greatly improving the energy density of the electrochemical device; at the same time, since the first positive electrode active material has a higher amount of lithium desorption in the high voltage region, it can reduce the risk of excessive lithium desorption of the second positive electrode active material in the high voltage region, thereby improving the structural stability of the second positive electrode active material at high temperature and high voltage, and due to the presence of oxygen vacancies on the surface of the first positive electrode active material itself, it can inhibit the release of oxygen on its surface, so that it still has a higher structural stability at high temperature and high voltage, so that the electrochemical device can have both good cycle performance and safety performance.

[0028] In some embodiments, the peak area of ​​peak a is S a , the peak area of ​​peak b is S b , satisfying: 0.4≤S a / S b ≤1.S a / S b It can be used to indirectly characterize the mixing ratio of the first positive electrode active material and the second positive electrode active material. By adjusting the relative content of the first positive electrode active material and the second positive electrode active material, the area ratio of peak a to peak b is S a / S b Meeting the above range can significantly improve the energy density of the electrochemical device while enabling the electrochemical device to have both excellent cycle performance and safety performance. a / S bis 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, or any two of the above. Further, in some embodiments, 0.45≤S a / S b ≤0.65.

[0029] In some embodiments, when the electrochemical device is in a fully charged state, the positive electrode plate is characterized by X-ray diffraction, and has two diffraction peaks in the range of 18° to 19.5°, which are diffraction peak A and diffraction peak B from low angle to high angle, and the peak intensity of diffraction peak A is I A , the peak intensity of diffraction peak B is I B , satisfying: 1.2≤I B / I A ≤5. Among them, the diffraction peak A corresponds to the first positive electrode active material, and the diffraction peak B corresponds to the second positive electrode active material. B / I A When the above range is met, the energy density of the electrochemical device can be greatly improved while the electrochemical device has excellent cycle performance and safety performance. B / I A ≤5. At this time, the cycle performance and safety performance of the electrochemical device are better.

[0030] In some embodiments, the first positive electrode active material includes a lithium nickel manganese composite oxide, and the second positive electrode active material includes a lithium cobalt composite oxide.

[0031] In some embodiments, the first positive electrode active material is a secondary particle aggregated from primary particles, so as to improve the kinetic performance of the electrochemical device.

[0032] In some embodiments, the first positive active material has an average diameter of 6 μm to 14 μm.

[0033] In some embodiments, the second positive active material is a primary particle.

[0034] In some embodiments, the second positive active material has an average diameter of 10 μm to 25 μm.

[0035] In some embodiments, in the cross section in the thickness direction of the positive electrode active material layer, the area of ​​the first positive electrode active material in the region of 127μm×34μm is S1, and the area of ​​the second positive electrode active material is S2, satisfying: 1≤S2 / S1≤7. S2 / S1 satisfies the above range, which can greatly improve the energy density of the electrochemical device while enabling the electrochemical device to have excellent cycle performance and safety performance. Optionally, S2 / S1 is 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7 or a range consisting of any two of the above. Further, in some embodiments, 3.4≤S2 / S1≤6.8. At this time, the cycle performance and safety performance of the electrochemical device are better.

[0036] In some embodiments, the first positive electrode active material further contains an M1 element, and M1 includes at least one of Na or K. The doping of the M1 element enables the first positive electrode active material to have good structural stability at high temperature and high voltage, thereby improving the cycle performance and safety performance of the electrochemical device. In some embodiments, based on the metal elements other than the Li element and the M1 element in the first positive electrode active material, the molar percentage of the Ni element in the first positive electrode active material is a1, the molar percentage of the Mn element is b1, and the molar percentage of the M1 element is c1, satisfying: 30% ≤ a1 ≤ 70%, 30% ≤ b1 ≤ 70%, 0.1% ≤ c1 ≤ 15%.

[0037] In some embodiments, the first positive electrode active material includes a substrate and a coating layer located on the surface of the substrate, wherein the coating layer contains element B. The coating layer containing the boron compound can neutralize the free lithium on the surface of the substrate on the one hand, and on the other hand, can eliminate HF generated by the decomposition of lithium salts or other side reactions in the electrochemical device, reduce the corrosion of HF on the electrode material and the current collector, and thus improve the cycle performance and high temperature storage performance of the electrochemical device.

[0038] In some embodiments, the coating layer comprises a B-containing oxide.

[0039] In some embodiments, based on the metal elements other than Li and M1 in the first positive electrode active material, the molar percentage of the B element in the first positive electrode active material is d1, 0.5%≤d1≤10%. Optionally, d1 is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 8%, 9%, 10% or a range consisting of any two of the above. Further, in some embodiments, 1.5%≤d1≤7%.

[0040] In some embodiments, the first cathode active material has a layered crystal structure belonging to the R-3m space group. In some embodiments, the first cathode active material includes Li x1 M1m Ni y1 Mn z1 B k R1 q1 O 2±n1 T1 n1 , 0.6≤x1≤1.2, 0.001≤m≤0.15, 0.3≤y1≤0.7, 0.3≤z1≤0.7, 0≤k≤0.1, 0≤q1≤0.2, 0≤n1≤0.2, wherein the element M1 includes at least one of Na or K, the element R1 includes at least one of Co, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and the element T1 includes at least one of F, Cl, Br, I or N.

[0041] In some embodiments, based on the metal elements other than Li in the second positive electrode active material, the molar percentage of the Co element in the second positive electrode active material is a2, satisfying: 80%≤a2≤100%.

[0042] In some embodiments, the second positive electrode active material further includes an M2 element, M2 includes at least one of Ni, Mn, Al, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and based on the metal elements other than Li element in the second positive electrode active material, the molar percentage of the M2 element in the second positive electrode active material is b2, satisfying: 0.1%≤b2≤20%.

[0043] In some embodiments, the second cathode active material has a layered crystal structure belonging to the R-3m space group. In some embodiments, the second cathode active material includes Li x2 Co y2 M2 z2 O 2±n2 T2 n2 , 0.6≤x2≤1.2, 0.8≤y2≤1, 0≤z2≤0.2, 0≤n2≤0.2, wherein element M2 includes at least one of Ni, Mn, Al, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and element T2 includes at least one of F, Cl, Br, I or N.

[0044] In some embodiments, the positive electrode plate may further include a positive electrode current collector, in which case the positive electrode active material layer may be located on one or both sides of the positive electrode current collector. In some embodiments, the positive electrode current collector may include aluminum foil, and of course, other positive electrode current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive electrode current collector is 7 μm to 20 μm.

[0045] In some embodiments, the positive electrode active material layer may further include a conductive agent and a binder. In some embodiments, the conductive agent includes at least one of acetylene black, carbon black, Ketjen black, carbon nanotubes, graphene or carbon nanofibers. In some embodiments, the binder may include polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, a styrene-acrylate copolymer, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the mass ratio of the positive active material, the conductive agent and the binder in the positive electrode active material layer is (90-99): (0.1-10): (0.1-10), but this is only an example, and any other suitable mass ratio may be used.

[0046] In some embodiments, the electrochemical device further comprises a negative electrode sheet and a separator, and the positive electrode sheet and the negative electrode sheet are separated by a separator disposed therebetween. In some embodiments, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer. In some embodiments, the negative electrode active material layer may be disposed on one side or both sides of the negative electrode current collector.

[0047] In some embodiments, the negative electrode active material layer may include a negative electrode active material, a binder, and an optional conductive agent. In some embodiments, the negative electrode active material may include at least one of a carbon material or a silicon-based material. In some embodiments, the carbon material includes at least one of graphite, hard carbon, soft carbon, or mesophase carbon microspheres. In some embodiments, the silicon-based material includes at least one of silicon, silicon-oxygen material, silicon-carbon material, or silicon-oxygen-carbon material.

[0048] In some embodiments, the binder in the negative electrode active material layer may include at least one of sodium carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, styrene-butadiene rubber, polyurethane resin or acrylate polymer. In some embodiments, the conductive agent in the negative electrode active material layer may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene or carbon nanofibers. In some embodiments, the mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode active material layer may be (78 to 98.5): (0.1 to 10): (0.1 to 10). It should be understood that the above is only an example, and any other suitable material and mass ratio may be used. In some embodiments, the negative electrode current collector may be at least one of copper foil, nickel foil or carbon-based current collector.

[0049] In some embodiments, the isolation membrane includes a porous substrate layer and a heat-resistant layer, and the heat-resistant layer is located on the surface of the porous substrate layer. In some embodiments, the porous substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide or aramid. In some embodiments, the thickness of the isolation membrane is in the range of 3 μm to 20 μm. In some embodiments, the pores of the porous substrate layer have a diameter in the range of 0.01 μm to 1 μm.

[0050] In some embodiments, the heat-resistant layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. The binder of the heat-resistant layer is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, or polyhexafluoropropylene.

[0051] In some embodiments, the isolation film further comprises an adhesive layer, and the adhesive layer is located on the surface of the porous substrate layer and / or the heat-resistant layer. In some embodiments, the adhesive layer comprises at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene.

[0052] In some embodiments, the electrochemical device includes a lithium-ion battery, but the application is not limited thereto.

[0053] In some embodiments, the electrochemical device further comprises an electrolyte, the electrolyte comprising a lithium salt and a non-aqueous solvent. In some embodiments, the lithium salt comprises lithium hexafluorophosphate. In some embodiments, the concentration of the lithium salt is 1 mol / L to 2 mol / L. In some embodiments, the non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, or a combination thereof.

[0054] In certain embodiments, carbonate compounds can be linear carbonate compounds, cyclic carbonate compounds or combinations thereof. Examples of linear carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or combinations thereof. Examples of carboxylic acid ester compounds are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, caprolactone, methyl formate or combinations thereof. Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0055] In the second aspect of the present application, an electronic device including the above-mentioned electrochemical device is also provided. The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0056] Taking lithium-ion batteries as an example, some specific embodiments and comparative examples are listed below to better illustrate the present application.

[0057] Example 1

[0058] Preparation of negative electrode sheet: artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 96:2:2 and dispersed in deionized water to prepare a negative electrode slurry with a solid content of 0.8. After stirring evenly, the negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil, and dried at 80°C to obtain a negative electrode sheet coated with a negative electrode active material layer on one side. Repeat the above steps on the other side of the copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. After cold pressing, striping and welding of the pole ears, the negative electrode sheet is obtained.

[0059] Preparation of positive electrode sheet: positive electrode active material (including the first positive electrode active material and the second positive electrode active material, the mixing mass ratio is shown in Table 1), conductive carbon black, carbon nanotubes and polyvinylidene fluoride are mixed in a mass ratio of 93.7:2.8:1.2:2.3 and dispersed in N-methylpyrrolidone to prepare a positive electrode slurry with a solid content of 0.7. After fully stirring and mixing, the positive electrode slurry is evenly coated on one side of the positive electrode current collector aluminum foil, and dried at 85°C to obtain a positive electrode sheet coated with a positive electrode active material layer on one side, and the above steps are repeated on the other side of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. After cold pressing, stripping, and welding of the pole ears, a positive electrode sheet is obtained.

[0060] The steps for preparing the first positive electrode active material are as follows:

[0061] 1) A mixed solution containing NiSO4 and MnSO4 is prepared according to the element molar ratio Ni:Mn=50:50, and the mixed solution is mixed with a precipitant (NaOH solution) and a complexing agent (ammonia water) for reaction, and the reaction time is controlled to be 60 hours, the ammonia concentration is 1 mol / L, and the pH value is 12.2 to obtain a nickel-manganese precursor TM(OH)2 (TM=Ni / Mn) with an average particle size Dv50 of 11 μm;

[0062] 2) Grind and mix the nickel-manganese precursor and sodium carbonate in a molar ratio of Na:(Ni+Mn) of 1.05:1. Calcine at 800°C in air for 20 hours, and then crush, screen and demagnetize to obtain product 1;

[0063] 3) mixing the product 1 with a mixture of lithium hydroxide and lithium nitrate (molar ratio of 1:1), wherein the mass ratio of the mixture of lithium hydroxide and lithium nitrate to the product 1 is 10:1, heating to 400°C at a rate of 10°C / min, maintaining for 6 hours, and quenching to room temperature in a mixture of Ar and air (the volume ratio of Ar to air is 1:2) at a cooling rate of 50°C / min to obtain the product 2;

[0064] 4) washing and soaking the second product in deionized water, and drying; 5) finally crushing and sieving to obtain the first positive electrode active material, wherein the Na / (Ni+Mn) molar ratio is 10.7%, and Dv50 is 9.4 μm.

[0065] The second positive electrode active material uses lithium cobalt oxide with a Dv50 of 21.7 μm.

[0066] Preparation of isolation membrane: A porous polyethylene (PE) film with a thickness of 8 μm was selected as the isolation membrane.

[0067] Preparation of electrolyte: In an argon atmosphere glove box with a water content of less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): propyl propionate (PP): ethyl propionate (EP) = 1:1:1:1:1, weight ratio) are uniformly mixed to prepare an electrolyte, wherein the mass percentage of lithium hexafluorophosphate in the electrolyte is 12.5%.

[0068] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, shaping, etc.

[0069] The difference between Examples 2 to 9 and Example 1 is that the composition of the positive electrode active material is adjusted according to the mass mixing ratio of the first positive electrode active material and the second positive electrode active material shown in Table 1.

[0070] The difference between Comparative Example 1 and Example 1 is that the positive electrode active material only uses the first positive electrode active material.

[0071] The difference between Comparative Example 2 and Example 1 is that the positive electrode active material only uses the second positive electrode active material.

[0072] The difference between Comparative Example 3 and Example 1 is that the first positive electrode active material is LiNi with a Dv50 of 12.9 μm. 0.92 Co 0.06 Mn 0.02 O2 secondary particles, where the average diameter of the primary particles is 0.6μm.

[0073] The difference between Examples 10 to 15 and Example 1 is that the first positive electrode active material is prepared according to the following method, and the first positive electrode active material is B-coated.

[0074] 1) A mixed solution containing NiSO4 and MnSO4 is prepared according to the element molar ratio of Ni:Mn=50:50, and the mixed solution is mixed with a precipitant (NaOH solution) and a complexing agent (ammonia water) to react, and a nickel-manganese precursor TM(OH)2 (TM=Ni / Mn) having an average particle size Dv50 of 11 μm is obtained by controlling the reaction time to 60 hours, the ammonia concentration to 1 mol / L, and the pH value to 12.2;

[0075] 2) Grind and mix the nickel-manganese precursor and sodium carbonate in a molar ratio of Na:(Ni+Mn) of 1.05:1. Calcine at 800°C in air for 20 hours, and then crush, screen and demagnetize to obtain product 1;

[0076] 3) mixing the product 1 with a mixture of lithium hydroxide and lithium nitrate (molar ratio of 1:1), wherein the mass ratio of the mixture of lithium hydroxide and lithium nitrate to the product 1 is 10:1, heating to 400°C at a rate of 10°C / min, maintaining for 6 hours, and quenching to room temperature in a mixture of Ar and air (the volume ratio of Ar to air is 1:2) at a cooling rate of 50°C / min to obtain the product 2;

[0077] 4) washing and soaking the product 2 in deionized water, and drying; crushing and sieving to obtain the product 3;

[0078] 5) Grind and mix the product 3 and boric acid in the ratio d1 shown in Table 2, and calcine them at 200° C. in an air atmosphere for 12 h to obtain a first positive electrode active material.

[0079] In addition, in this application, the following method is used to measure the corresponding parameters.

[0080] 1) Peak area:

[0081] In the voltage range of 3V to 4.45V, the lithium-ion battery is charged and discharged with a current of 0.1C to obtain a curve of the relationship between the discharge capacity-voltage differential dQ / dV and the voltage V. Peak a and peak b in the curve are integrated to obtain the peak areas of the corresponding peaks.

[0082] 2) Particle morphology, average diameter and area ratio S2 / S1:

[0083] The positive electrode sheet was cut longitudinally using ion polishing, and then the morphology of the positive electrode active material particles in the cross section of the positive electrode sheet was observed using a scanning electron microscope (instrument model: ZEISS SEM, acceleration voltage: 0.1KV to 30KV). In the cross-sectional photo, 50 first or second positive electrode active material particles were randomly selected, and the average value of their longest diameters was taken as the average diameter of the first or second positive electrode active material.

[0084] In the cross-sectional photograph, a region of 127 μm×34 μm was randomly selected, and image software was used to count the area of ​​the first positive electrode active material as S1 and the area of ​​the second positive electrode active material as S2, thereby calculating the area ratio S2 / S1.

[0085] 3) Element content:

[0086] For the initial positive electrode active material, a mixed solvent was used to dissolve the first and second positive electrode active materials respectively (for example, 0.4 g of the positive electrode active material was dissolved in a mixed solvent of 10 ml of aqua regia (nitric acid and hydrochloric acid mixed in a ratio of 1:1) and 2 ml of HF), the volume was fixed to 100 mL, and then the content of each element in the solution was tested using an ICP analyzer.

[0087] For the first positive electrode active material and the second positive electrode active material in the positive electrode sheet, the positive electrode sheet was cut longitudinally using ion polishing, and then the cross-section of the positive electrode sheet was observed using a scanning electron microscope (instrument model: ZEISS SEM), and the first and second positive electrode active materials were tested respectively using an energy dispersive spectrometer (EDS) to determine the element content in the first positive electrode active material and the second positive electrode active material.

[0088] 4) X-ray diffraction:

[0089] The lithium-ion battery was fully discharged and disassembled to obtain the positive electrode piece, and the positive electrode piece was subjected to X-ray diffraction analysis using an X-ray diffractometer (instrument model: Bruker D8ADVANCE, target material: Cu Kα, scanning angle: 5-80°).

[0090] 5) Discharge capacity test:

[0091] The lithium-ion battery is first charged at a constant current of 0.5C at a constant temperature of 25°C. After charging to 4.45V, it is charged at a constant voltage of 4.45V to a current of 0.05C. Then, it is discharged at a constant current of 0.2C to 3V. The discharge gram capacity = 0.2C first discharge capacity / mass of the positive electrode active material.

[0092] 6) Cycle performance test:

[0093] First, in an environment of 45°C, the first charge and discharge were performed, first using a 0.5C current for constant current charging, charging to 4.45V, then performing a 4.45V constant voltage charge to a current of 0.05C, and then performing a constant current discharge at a current of 0.5C to 3V. Repeat the above charge and discharge cycles, and record the discharge capacity of the 3rd cycle and the discharge capacity of the 500th cycle.

[0094] 45° C. cycle capacity retention rate=(discharge capacity at the 500th cycle / discharge capacity at the 3rd cycle)×100%.

[0095] 7) High temperature storage performance test:

[0096] First, the lithium-ion battery is charged with a constant current of 0.5C at 25°C. After charging to 4.45V, it is charged with a constant voltage of 4.45V to a current of 0.05C. The thickness of the lithium-ion battery is measured with a micrometer, and the thickness of the lithium-ion battery at this time is defined as the initial thickness H0 of the lithium-ion battery. The lithium-ion battery is then stored in a constant temperature box at 85°C for 24 hours, and the thickness of the lithium-ion battery is measured using the same method. The thickness of the lithium-ion battery after storage is defined as H1.

[0097] 85℃ thickness expansion ratio = (H1-H0) / H0×100%.

[0098] Table 1 shows various parameters and evaluation results of Examples 1 to 9 and Comparative Examples 1 to 3.

[0099] Table 1

[0100]

[0101]

[0102] By comparing Examples 1 to 9 and Comparative Example 2, it can be seen that the discharge gram capacity of the lithium ion batteries of Examples 1 to 9 is improved compared with Comparative Example 2 which does not use the first positive electrode active material.

[0103] By comparing Examples 1 to 9 and Comparative Example 1, it can be seen that the high temperature cycle capacity retention rate and high temperature thickness expansion rate of the lithium ion batteries of Examples 1 to 9 are significantly improved compared with Comparative Example 1 which does not use the second positive electrode active material.

[0104] By comparing Example 1 and Comparative Example 3, it can be seen that, compared with the conventional mixed system of high-nickel ternary materials and lithium cobalt oxide, the mixed system of the first positive electrode active material and lithium cobalt oxide of the present application can significantly improve the high-temperature cycle performance and high-temperature storage performance of lithium-ion batteries on the basis of greatly improving the discharge gram capacity.

[0105] In addition, it can be seen from Examples 1 to 9 that when 0.4≤S a / S b ≤1,1.2≤I B / I A When ≤5 or 1≤S2 / S1≤7, the lithium-ion battery has a high discharge capacity, good cycle capacity retention and low thickness expansion rate. a / S b ≤0.65, 2≤I B / I AWhen ≤5 or 3.4≤S2 / S1≤6.8, the high temperature cycle performance and high temperature storage performance of lithium-ion batteries are better.

[0106] Table 2 shows various parameters and evaluation results of Example 1 and Examples 10 to 15.

[0107] Table 2

[0108]

[0109] By comparing Example 1 with Examples 10 to 15, it can be seen that by coating the first positive electrode active material with B, the high-temperature cycle capacity retention rate of the lithium-ion battery is significantly improved, and the high-temperature storage thickness expansion rate is significantly reduced. It can be seen that by coating the first positive electrode active material with B, the high-temperature cycle performance and safety performance of the lithium-ion battery can be greatly improved. The possible reason is that the surface of the first positive electrode active material is coated with a boron-containing compound, which neutralizes the free lithium on the surface of the material on the one hand, and eliminates HF generated by the decomposition of lithium salts and other side reactions in the battery on the other hand, thereby improving the high-temperature cycle performance and high-temperature storage performance of the battery.

[0110] The above description is only a preferred embodiment of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application are included in the protection scope of the present application.

Claims

1. An electrochemical device, characterized in that A positive electrode sheet is included, wherein the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material, the first positive electrode active material contains Ni and Mn elements, and the second positive electrode active material contains Co elements; The relationship curve between the capacity-voltage differential dQ / dV and the voltage V of the electrochemical device during discharge includes a peak a with a peak position between 4.1V and 4.3V and a peak b with a peak position between 3.6V and 4.0V.

2. The electrochemical device according to claim 1, characterized in that The peak area of ​​peak a is S a , the peak area of ​​peak b is S b , satisfying: 0.4≤S a / S b ≤1.

3. The electrochemical device according to claim 2, characterized in that 0.45≤S a / S b ≤0.65。 4. The electrochemical device according to claim 1, characterized in that When the electrochemical device is in a fully charged state, the positive electrode plate is characterized by X-ray diffraction, and has two diffraction peaks in the range of 18° to 19.5°, which are diffraction peak A and diffraction peak B from low angle to high angle, and the peak intensity of the diffraction peak A is I A , the peak intensity of the diffraction peak B is I B , satisfying: 1.2≤I B / I A ≤5.

5. The electrochemical device according to claim 4, characterized in that 2≤I B / I A ≤5。 6. The electrochemical device according to claim 1, characterized in that The electrochemical device satisfies at least one of the following conditions: (1) The first positive electrode active material includes a lithium nickel manganese composite oxide, and the second positive electrode active material includes a lithium cobalt composite oxide; (2) The first positive electrode active material is a secondary particle aggregated from primary particles; (3) The average diameter of the first positive electrode active material is 6 μm to 14 μm; (4) The second positive electrode active material is a primary particle; (5) The average diameter of the second positive electrode active material is 10 μm to 25 μm; (6) The first positive electrode active material has a layered crystal structure belonging to the R-3m space group; (7) The second positive electrode active material has a layered crystal structure belonging to the R-3m space group.

7. The electrochemical device according to claim 1, characterized in that In the cross section of the positive electrode active material layer in the thickness direction, the area of ​​the first positive electrode active material in the region of 127 μm×34 μm is S1, and the area of ​​the second positive electrode active material is S2, satisfying: 1≤S2 / S1≤7.

8. The electrochemical device according to claim 1, characterized in that The electrochemical device satisfies at least one of the following conditions: (1) The first positive electrode active material further contains an M1 element, M1 includes at least one of Na or K, and based on the metal elements other than Li and M1 in the first positive electrode active material, the molar percentage of Ni in the first positive electrode active material is a1, the molar percentage of Mn is b1, and the molar percentage of M1 is c1, satisfying: 30%≤a1≤70%, 30%≤b1≤70%, 0.1%≤c1≤15%; (2) The first positive electrode active material includes Li x1 M1 m Ni y1 Mn z1 B k R1 q1 O 2±n1 T1 n1 , 0.6≤x1≤1.2, 0.001≤m≤0.15, 0.3≤y1≤0.7, 0.3≤z1≤0.7, 0≤k≤0.1, 0≤q1≤0.2, 0≤n1≤0.2, wherein the element M1 includes at least one of Na or K, the element R1 includes at least one of Co, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and the element T1 includes at least one of F, Cl, Br, I or N; (3) Based on the metal elements other than Li in the second positive electrode active material, the molar percentage of the Co element in the second positive electrode active material is a2, satisfying: 80%≤a2≤100%; (4) The second positive electrode active material further comprises an M2 element, wherein M2 comprises at least one of Ni, Mn, Al, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and based on the metal elements other than Li in the second positive electrode active material, the molar percentage of the M2 element in the second positive electrode active material is b2, satisfying: 0.1%≤b2≤20%; (5) The second positive electrode active material includes Li x2 Co y2 M2 z2 O 2±n2 T2 n2 , 0.6≤x2≤1.2, 0.8≤y2≤1, 0≤z2≤0.2, 0≤n2≤0.2, wherein element M2 includes at least one of Ni, Mn, Al, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge, and element T2 includes at least one of F, Cl, Br, I or N.

9. The electrochemical device according to claim 1, characterized in that The first positive electrode active material includes a substrate and a coating layer located on the surface of the substrate, the coating layer contains B, and the electrochemical device satisfies at least one of the following conditions: (1) The coating layer comprises B oxide; (2) Based on the metal elements other than Li and M in the first positive electrode active material, the molar percentage content of B in the first positive electrode active material is d1, and 0.5%≤d1≤10%.

10. An electronic device comprising the electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Positive electrode material, electrochemical device comprising same, and electronic device

    CN113224271A

  • Positive electrode material, and electrochemical device and electronic device including positive electrode material

    CN116325219A

  • Electrochemical device and electronic apparatus

    CN116802845A

  • Composite positive active material, positive electrode including the same, and lithium battery including the positive electrode

    KR1020160010297A

Cited By

  • Secondary battery and electronic apparatus

    WO2026129186A1

  • Secondary battery and electronic apparatus

    WO2026165941A1

  • Secondary battery and electronic apparatus

    WO2026188491A1